2010
DOI: 10.1118/1.3468702
|View full text |Cite
|
Sign up to set email alerts
|

SU‐GG‐T‐306: Can Single Dataset in Treatment Planning System Represent Several Beam‐Matched Accelerators?

Abstract: Purpose: Beam matched accelerators can provide the flexibility within the radiotherapy department. Furthermore, the accelerators could be represented by single beam data set in the treatment planning system (TPS). The aim of this study was to evaluate the match between dosimetrical characteristics of Elekta accelerators. Method and Materials: The data from three accelerators was used in analysis. Three photon and six electron beams were matched according to the vendor specification. The first accelerator data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…It is not enough to rely only on the vendor beam-matching criteria, and very strict criteria needs to be implemented to obtain a satisfactory match. This has been shown by several authors [ 15 17 ].…”
Section: Opening Statement – Jerome Gastaldosupporting
confidence: 76%
“…It is not enough to rely only on the vendor beam-matching criteria, and very strict criteria needs to be implemented to obtain a satisfactory match. This has been shown by several authors [ 15 17 ].…”
Section: Opening Statement – Jerome Gastaldosupporting
confidence: 76%
“…For a department that wishes to beam match their linear accelerator fleet to a degree beyond VMAT that allows for distributive QA and delivery of SBRT, the following items are recommended: Profiles and PDDs should be matched to criteria that is stricter than vendor guidelines . For example, the linacs in this study were matched at commissioning with PDD 20,10 matching <0.5% and all points in the PDD within 0.5% of the reference curve.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that matching a new linac to a reference linac does not guarantee that it is matched to the established treatment planning model. Similarly, Gersgjevitsh et al . demonstrated that a single TPS model could not be supported by their three Elekta linacs which were matched according to the vendor's beam matching criteria, calling for stricter criteria and an additional subset of dosimetric data to be matched to if a single model was to be used.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the gamma analysis with vendor‐provided criteria were insufficient for the purpose of beam matching, and stricter gamma criteria were recommended. 4 , 6 , 7 , 8 To ensure clinically sufficient beam matching, it was insisted that the beam data of each linac should not be matched to that of the reference linac, but the TPS calculation should be used as the reference. 4 Furthermore, it was recommended that the calculation by TPS beam model may be employed as the reference.…”
Section: Discussionmentioning
confidence: 99%